Umpan balik dan Evaluasi Terhadap kinerja Organisasi: A Literature Review - Mahyadi Mahyadi; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2023)
Feedback is information provided to individuals about their performance and can help them understand the difference between desired performance and actual performance achieved. Individuals with high self-evaluation tend to assess job demands in a more positive manner and have a greater ability to face or overcome those demands. High self-evaluation can influence individuals' perceptions of work situations and have a positive impact on job satisfaction. This systematic review is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The databases used were Scopus, SAGE full-text articles, and the language of publication was English. The keywords used in the article search were